2021
DOI: 10.1097/j.jcrs.0000000000000540
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of intraocular lens calculation formulas for flanged intrascleral intraocular lens fixation with double-needle technique

Abstract: Refractive prediction errors for eyes undergoing the Yamane double-needle technique were not statistically significantly different between IOL calculation formulas. Error ranged from hyperopic to predicted values for all formulas tested.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 8 publications
4
15
0
Order By: Relevance
“…In this study, SE showed a hyperopic shift of 0.44 ± 1.00 D after ISF. In a previous study by McMillin et al [ 28 ], SE after ISF showed a 0.57 D hyperopic shift compared with the predicted SE using the SRK-T formula, which is consistent with the results of this study.…”
Section: Discussionsupporting
confidence: 93%
“…In this study, SE showed a hyperopic shift of 0.44 ± 1.00 D after ISF. In a previous study by McMillin et al [ 28 ], SE after ISF showed a 0.57 D hyperopic shift compared with the predicted SE using the SRK-T formula, which is consistent with the results of this study.…”
Section: Discussionsupporting
confidence: 93%
“…Te principle of the three formulas might account for the results because these formulas were introduced to predict IOL power within the capsular bag; however, the fxation sites in the present technique were 2.0 mm posterior to the limbus, anterior to the intracapsular implantation position, leading to myopic errors. Te reported MAE following intrascleral or transscleral fxation using the thirdgeneration formulas was 0.61 to 0.86 D, which agreed with our results [30,31]; whereas the values of MAE in our series were larger than those of routine cataract surgery, suggesting the compromised performance of formulas when the IOL was placed outside the capsular bag [32]. Previous studies reported that 30% to 45% of eyes with a PE within ±0.5 D in patients receiving fanged or transscleral-sutured fxation, in accordance with our study (43.48%) [30,33].…”
Section: Discussionsupporting
confidence: 92%
“…Te reported MAE following intrascleral or transscleral fxation using the thirdgeneration formulas was 0.61 to 0.86 D, which agreed with our results [30,31]; whereas the values of MAE in our series were larger than those of routine cataract surgery, suggesting the compromised performance of formulas when the IOL was placed outside the capsular bag [32]. Previous studies reported that 30% to 45% of eyes with a PE within ±0.5 D in patients receiving fanged or transscleral-sutured fxation, in accordance with our study (43.48%) [30,33]. Furthermore, for cases following fanged or transscleral-sutured fxation, the percentage of a PE within ±1.0 D was approximately 60% to 75% [30,33].…”
Section: Discussionsupporting
confidence: 92%
“…27 Similarly, MAE were found to be more than 0.70 D with a flanged intrascleral IOL fixation, suggesting that, in cases where IOLs that were not implanted in the capsular bag, the accuracy of these formulas could be compromised. 30 Classic scleral IOL fixation and newer flanged intrascleral IOL fixation techniques are widely used in eyes with insufficient capsular support, and large sample multicenter studies and new IOL formulas are therefore required in these cases.…”
Section: Discussionmentioning
confidence: 99%